The Role of Human Rights in Shaping Asia-Pacific Policies and Strategies: A Criminal Law Perspective - Mikhael Feka; Pujiyono; R.B Sularto; Zico Junius Fernando (Universitas Negeri Semarang, 2024)
The Asia-Pacific region, with its complex cultural, social, and political diversity, faces significant challenges in integrating human rights into criminal law policies and strategies. This study aims to analyze the role of human rights in shaping criminal law policies and strategies in this region, focusing on the protection of the rights of the accused, the right to a fair trial, and the protection of crime victims. The background of this research is the increasing global pressure on Asia-Pacific countries to implement international human rights standards within their criminal justice systems, amidst the diverse legal systems present in the region. This research utilizes normative legal methods by adopting statutory, conceptual, comparative, approaches. The nature of this research is descriptive-prescriptive. The data that has been collected is analyzed using the content analysis method. The findings indicate that, despite significant efforts to adopt human rights standards, challenges such as political instability, economic disparities, and differing legal traditions remain major obstacles. Additionally, the study finds that the implementation of restorative justice principles could be an effective solution to enhancing human rights protection within the context of criminal law in the Asia-Pacific region. Overall, this study concludes that, despite the complex challenges, strengthening international cooperation and commitment to the rule of law can better facilitate the integration of human rights into criminal law policies and strategies in the Asia-Pacific region. The findings provide crucial recommendations for policymakers and legal practitioners in their efforts to create a more just and humane criminal justice system.